2014
DOI: 10.1590/2175-7860201465314
|View full text |Cite
|
Sign up to set email alerts
|

Espécies raras e comuns de Myrtaceae da Floresta Estacional Decidual de Santa Catarina, Brasil

Abstract: ResumoObjetivou-se avaliar as espécies arbóreas raras e comuns da família Myrtaceae amostradas pelo Inventário Florístico Florestal de Santa Catarina na Floresta Estacional Decidual. Esta floresta ocorre ao longo do rio Uruguai e afluentes, sob baixas temperaturas no inverno e chuvas bem distribuídas ao longo do ano, com árvores do dossel e emergentes predominantemente caducifólias. Coletaram-se dados em 78 unidades amostrais com 0,40 ha cada, registrando-se árvores com diâmetro na altura do peito ≥ 10 cm. Uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
6
0
5
Order By: Relevance
“…Macbr., C. canjerana, Nectandra lanceolata Nees, P. rigida and others (Fontana and Sevegnani, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Macbr., C. canjerana, Nectandra lanceolata Nees, P. rigida and others (Fontana and Sevegnani, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Depending on the variables analyzed, the concept of rarity can be considered rather broad and controversial, therefore the use of Rabinowitz et al (1986) seven rarity forms is an objective tool to distinguish priority areas for conservation by taking into account the particularities of environmental requirements for the species distribution (Caiafa & Martins 2010, Fontana et al 2014. In the CNP, a large percentage of species were categorized amongst the rarest forms (6 and 7), reflecting the restricted distribution usually found among Bromeliaceae (Versieux & Wendt 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The species with higher importance values are common and important in other surveys in the Araucaria and Seasonal forests of Santa Catarina (Gasper, Uhlmann, et al 2013, Gasper et al 2015, Vibrans et al 2011, Schneider & Rocha 2014, Vibrans et al 2013a, 2012. Ocotea diospyrifolia, Cupania vernalis, Casearia sylvestris, Diatenopteryx sorbifolia and Myrocarpus frondosus are common at Seasonal forest (Fontana & Sevegnani 2012) and A. angustifolia, Coussarea contracta e Cupania vernalis, are typical from components of early and intermediate successional stages in the Araucaria forest of Santa Catarina (Klauberg et al 2010, Vibrans et al 2011). According to Gasper et al (2015), Cupania vernalis, Diatenopteryx sorbifolia and Myrocarpus frondosus characterize the transitional forests from the west of Santa Catarina.…”
Section: Tree Community Structure and Composition In A Subtropical Fomentioning
confidence: 99%
“…Leyser et al (2009) demonstrated high species richness of Fabaceae and Lauraceae in the transitional area between Araucaria and Seasonal forest, as found in this study, which may also indicate an association between these families in ecotonal areas. In general, Myrtaceae species are widely distributed in Atlantic forest s.l., but with lower abundance in the SF of Santa Catarina, leading to a rare occurrence specially driven by the climatic filters in the region (Fontana et al 2014). These associations reflect complex species interactions which may also contribute powerfully to forest structuring and patterns of species distributions, leading to more studies and efforts in ecotonal areas.…”
Section: Familymentioning
confidence: 99%